TEPUNG IKAN TERI NASI (STOLEPHORUS COMMERSINI LAC.) SEBAGAI SUMBER KALSIUM DAN PROTEIN PADA CORN FLAKES ALTERNATIF SARAPAN ANAK USIA SEKOLAH - Rahmi, Yosfi; Widya, Novita; Anugerah, Paramita Nur; Tanuwijaya, Laksmi Karunia (Lembaga Penerbitan Unversitas Esa Unggul, 2018)
School-aged children need adequate nutrients to support their growth. Infact, the school-aged children in Indonesia eat a low nutritional breakfast, even many who do not eat breakfast. An alternative solution is the manufacture of cereals that are practical yet nutrient-dense as high in protein and calcium. The purpose of this study was to determine the protein, calcium contents and sensory properties of Corn Flakes based on anchovy flour as an alternative breakfast for school-aged Children. This research uses Completely Randomized Design (CRD). Treatment is the ratio of corn flour:anchovy flour that are 100:0, 90:10, 80:20, and 70:30. Each treatment was repeated 5 times. The results showed an increase in the concentration of anchovy flour gave a significant difference in protein content (Kruskal Wallis, p=0,000) and calcium (ANOVA, p=0,000) of Corn Flakes. However, the use of anchovy flour decreases the sensory properties of Corn Flakes in terms of color, texture, taste, and aroma (Kruskal-Wallis, p<0.05). Conclusion, the best Corn Flakes composition of corn flour with anchovy flour is 80:20 to obtain better sensory properties of Corn Flakes. Consumption of 30 g of Corn Flakes TITN per day can meet the protein and calcium needs of children aged 7-9 years by 8.96% and 45.99%.Â Keywords: Corn flakes, anchovy flour, protein, calcium, sensory properties.